1990
DOI: 10.1093/nar/18.6.1451
|View full text |Cite
|
Sign up to set email alerts
|

Human ureaplasmas show diverse genome sizes by pulsed-field electrophoresis

Abstract: Contour clamped homogeneous field (CHEF) agarose gel electrophoresis (AGE), ramped to give linear separation of DNA molecules of 600-1600 kilobase pairs (kbp), was used to determine mobilities for full-sized genomic DNA of the serotype standard strains of the human genital mollicutes, Ureaplasma urealyticum relative to yeast chromosomal DNA markers. Indicated genome sizes (in kbp) were 760 for the four biotype 1 strains and 840-1140 for eleven biotype 2 strains. Other estimates were: 720 for Mycoplasma hominis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 32 publications
3
36
0
2
Order By: Relevance
“…Relative band fluorescence intensities and later hybridization data indicated that band Sa5 contained three fragments of similar size ; these fragment names are distinguished by the letters a, b and c. Sizes of the bands were determined by averaging the measurements from several gels. The size of the M. flocculare genome, as determined by averaging the totals from each of the restriction digests, was determined to be approximately 900 kb ; this is in agreement with previous reports (Robertson et al, 1990). The order of the restriction fragments from each digest on the M. flocculare chromosome was determined by examining hybridization (and therefore overlap) between individual fragments from different digests (Table 1).…”
Section: Construction Of the M Flocculare Genomic Mapsupporting
confidence: 86%
See 1 more Smart Citation
“…Relative band fluorescence intensities and later hybridization data indicated that band Sa5 contained three fragments of similar size ; these fragment names are distinguished by the letters a, b and c. Sizes of the bands were determined by averaging the measurements from several gels. The size of the M. flocculare genome, as determined by averaging the totals from each of the restriction digests, was determined to be approximately 900 kb ; this is in agreement with previous reports (Robertson et al, 1990). The order of the restriction fragments from each digest on the M. flocculare chromosome was determined by examining hybridization (and therefore overlap) between individual fragments from different digests (Table 1).…”
Section: Construction Of the M Flocculare Genomic Mapsupporting
confidence: 86%
“…M. hyopneumoniae is the causative agent of enzootic pneumonia in pigs, a chronic and highly transmissible disease found in swine herds worldwide, while M. flocculare is generally regarded as a commensal organism (Kobisch & Friis, 1996). The genome of M. hyopneumoniae was found to be larger (1070 compared with 890 kb) by pulsed-field gel electrophoresis (Robertson et al, 1990) and its pathogenicity is presumably facilitated by genes that are absent in M. flocculare. Comparison of detailed maps of the chromosomes of both species could identify chromosomal rearrangements and deletions that contain genes with potential as therapeutic or vaccination targets.…”
mentioning
confidence: 99%
“…On the basis of DNA reassociation kinetics, electron microscopy, and two-dimensional denaturing gradient gel electrophoresis studies, the genome sizes of mycoplasmas and ureaplasmas range from 600 to 800 kb and those of acholeplasmas and spiroplasmas range from 1,500 to 1,700 kb (1-3, 11, 12). More recent pulse-field gel electrophoresis (PFGE) data indicate greater diversity in the genome sizes of mycoplasmas and ureaplasmas, with a range of 600 to 1,300 kb (4,10,15,17). PFGE estimates for the sizes of acholeplasma genomes (10) (19).…”
mentioning
confidence: 99%
“…A common theme in pathogenic bacteria and parasites for maintaining surface variability is the utilization of multiple variable genes organized as gene families, allowing the generation of an extensive repertoire of antigenic variants (382,441). Oscillation of each individual gene between the ON and OFF expression states at high frequency, in conjunction with the ability of each gene to produce distinct size variants of its own product, means that numerous combinatorial antigenic repertoires can be generated on the surface of the organism.…”
Section: Gene Families As a Common Theme For Surface Diversificationmentioning
confidence: 99%